TAM Analysis on The Factors Affecting Admission of Students for Ruangguru Application - Riyan Latifahul Hasanah; Fanny Fatma Wati; Dwiza Riana (Jurnal Sistem Informasi, 2019)
A new paradigm emerged in the field of education along with the development of increasingly advanced technology, namely the emergence of an electronic learning system known as e-learning. One of the e-learning media that is currently popular in Indonesia is Ruangguru online learning application that can be accessed through smartphone. The purpose of this study is to analyze the factors that influence student’s acceptance of Ruangguru application using Technology Acceptance Model (TAM) method. The 5 (five) constructs of the TAM research model were used, namely Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Actual System Use, and Behavioral Intention of Use. The data collection used is an online questionnaire with purposive sampling technique. The results show that Attitude Towards Using did not have a significant effect on Behavioral Intention of Use, meaning that the students’ attitude towards using of did not affect students' intentions in using Ruangguru application. At the same time, the relationship of Perceived Ease of Use to Perceived Usefulness is the most significant influence where the ease in using Ruangguru application makes users feel that Ruangguru application is useful.